Progress in unipolar corona discharger designs for airborne particle charging: A literature review - Panich Intra (2018)
Particle motion induced by electrical forces is the basis for important class of measuring instruments. Charging is important in aerosol size measurement. Unipolar charger is a crucial component in the aerosol particle sizing system by electrical mobility analysis. For an electrical mobility analyzer, the charging is aimed to impose a known net charge distribution on each aerosol size. The charger performance depends on the charging efficiency and stable operation. A well-designed unipolar charger should provide high charging efficiency and stability that can be accurately determined for any given operating conditions. This article presents and discusses progress on the development of existing unipolar aerosol chargers based on corona discharge technique. The operating principles as well as detailed physical characteristics of these chargers, including the corona-wire and corona-needle chargers, are described with extensive list of references. © 2009 Elsevier B.V. All rights reserved.